The relationship of the investment environment with the indicators of the national economy (Journal of Accounting and Financial Studies ( JAFS ), 2021)
The investment environment is the incubator for all types of domestic and foreign investments, so if their determinants are encouraging, they increase the levels of investment flows and vice versa, as there is a relationship between the nature of the investment environment and the level of investment flows, and the determinants of the investment environment are numerous and the most important of which are security and political stability, and economic and financial factors that include relative stability In the exchange rate and inflation rates, the availability of banks and their development, transparency and integrity in administrative dealings and the lack of prevalence of administrative and financial corruption, and the clarity of legal and other procedures. Therefore, the importance of the environment is highlighted. Investment and its relationship to indicators of the national economy as one of the important strategic issues as it is the incubator in which the investment and the economy in general grows and develops. The Iraqi economy suffers from structural imbalances, as a result of the decline in crude oil prices, which makes the Iraqi economy a powerless economy in the face of fluctuations in the prices of oil derivatives, as total exports for the same year amounted to 49.4 billion dollars The share of oil exports was $49.1 billion. In 2017 and 2018, the total exports amounted to $60 and 85.2 billion, respectively. The share of oil exports was $59.6 and 83.8 billion, respectively, for two years. The value of imports increased from 37.1 billion dollars in 2014 to 48.6 billion dollars in 2016 and then to 37.0 billion dollars in 2018, while the proportion of imports to GDP was 28.7% in 2016 and then The value of imports was taken by fluctuation. Any decrease in crude oil prices will make the value of imports greater than the value of exports, and therefore the trade balance will be negative, which will cause the Iraqi economy to suffer major dilemmas, as it reached negative 4.8 billion dollars in 2016 and then rose positively to 48.2 billion dollars in 2018.